Innovative Methods And Practical Exercises For Developing Communicative Competence In The Uzbek Language - Abdunazarova Odina Toshqinboy qizi (Zien Journals, 2025)
the article analyzes innovative methods and practical exercises for developing communicative competence in Uzbek language lessons. The main objective of the study is to propose modern methods for improving speaking skills and to examine their effectiveness.
Keywords: communicative competence; innovative methods; speaking skills